2017
DOI: 10.1128/jvi.00625-17
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Upregulation Contributes to Porcine Reproductive and Respiratory Syndrome Virus Release

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) continues to cause substantial economic losses to the pig industry worldwide. Heparan sulfate (HS) is used by PRRSV for initial attachment to target cells. However, the role of HS in the late phase of PRRSV infection and the mechanism of virus release from host cells remain largely unknown. In this study, we showed that PRRSV infection caused a decrease in HS expression and upregulated heparanase, the only known enzyme capable of degrading HS. We subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…We suspect that inhibition of viral HPSE upregulation or removal of the protein altogether will produce large reductions in virulence and manifestations of disease. Recently, HPSE has been shown to be upregulated and activated in multiple viral infections (Hadigal et al, 2015; Puerta-Guardo et al, 2016; Guo et al, 2017), suggesting that our findings will likely also apply to other pathogens outside of the herpesvirus family. With several HPSE-blocking agents currently in phase 1 and 2 clinical trials for various cancers, targeting HPSE in infection could be an effective and attainable strategy for which there already exists a wealth of clinical information.…”
Section: Resultsmentioning
confidence: 76%
“…We suspect that inhibition of viral HPSE upregulation or removal of the protein altogether will produce large reductions in virulence and manifestations of disease. Recently, HPSE has been shown to be upregulated and activated in multiple viral infections (Hadigal et al, 2015; Puerta-Guardo et al, 2016; Guo et al, 2017), suggesting that our findings will likely also apply to other pathogens outside of the herpesvirus family. With several HPSE-blocking agents currently in phase 1 and 2 clinical trials for various cancers, targeting HPSE in infection could be an effective and attainable strategy for which there already exists a wealth of clinical information.…”
Section: Resultsmentioning
confidence: 76%
“…HSV-2 encodes two envelope glycoproteins, gB and gC, which bind HS at the cell surface and initiate viral entry (17)(18)(19). We first reported that host-encoded HPSE is upregulated and required for the release of viral progeny from parent cells after HSV-1 infection, and subsequently, similar findings were reported for porcine reproductive and respiratory syndrome virus (PRRSV) infection (20,21).…”
mentioning
confidence: 70%
“…In this regard, HSV-2 does not have any known viral proteins that can cleave cell surface HS. HSV-2 may have found the ability to cleave HS nevertheless from a host enzyme (20,21). Given that HPSE is the only known mam- malian enzyme capable of cleaving HS chains (9-11), we hypothesized and then demonstrated that its upregulation during infection may be beneficial for HSV-2 release from host cells.…”
Section: Discussionmentioning
confidence: 96%
“…HSV-2 encodes for two envelop glycoproteins, gB and gC, which bind HS at the cell surface and initiate viral entry (17-19). We first reported that host-encoded HPSE is upregulated and required for the release of viral progeny from parent cells after HSV-1 infection and subsequently similar findings were reported for porcine reproductive and respiratory syndrome virus (PRRSV) infection(20, 21).…”
Section: Introductionmentioning
confidence: 52%
“…In this regard, HSV-2 does not have any known viral proteins that can cleave cell surface HS. HSV-2 may have found the ability to cleave HS nevertheless from a host enzyme (20, 21). Given that HPSE is the only known mammalian enzyme capable of cleaving HS chains (9), we hypothesized and then demonstrated that its upregulation during infection may be beneficial for HSV-2 release from host cells.…”
Section: Discussionmentioning
confidence: 99%